The RNA polymerase PB2 subunit is not required for replication of the influenza virus genome but is involved in capped mRNA synthesis. - Nakagawa, Y (1995)
An established cell line, clone 64, in which the expression of the RNA polymerase PB1 and PA subunit genes and the nucleoprotein (NP) gene but not the PB2 subunit gene of influenza virus can be induced by the addition of dexamethasone, was used to analyze the replication and transcription machineries of the influenza virus. Both NS-CATc and NS-CATv, the chimeric nonstructural protein chloramphenicol acetyltransferase (NS-CAT) RNAs in the sense and antisense orientations positioned between the 5'- and 3'-terminal sequences of influenza virus RNA segment 8 (the NS gene), respectively, can be transcribed into the corresponding complementary-strand RNA in clone 64 cells only when treated with dexamethasone. Although sense-strand poly(A)+ CAT RNA was detected in the dexamethasone-treated clone 64 cells transfected with NS-CATv RNA, CAT activity was not detected in these cells and the isolated poly(A)+ CAT RNA was inert in an in vitro translation system. However, when the poly(A)+ CAT RNA was capped by using a purified yeast mRNA capping enzyme (mRNA guanylyltransferase), the capped poly(A)+ CAT RNA became translatable in the in vitro translation system. These results indicated that PB1, PA, and NP can support the replication of the influenza virus genome as well as the transcription to yield uncapped poly(A)+ RNA and that PB2 is specifically required for the synthesis of capped RNA.